Effects of the coagulation temperature on the properties of wet‐spun poly(vinyl alcohol)–graphene oxide fibers. Issue 43 (20th July 2017) - Hu, Chengming; Li, Jinlei; Liu, Dagang; Song, Renjie; Gu, Jiefan; Prempeh, Nana; Li, Huiyan
ABSTRACT: Graphene oxide (GO) as a positive reinforcement filler was dispersed into a poly(vinyl alcohol) (PVA) dope and wet‐spun into composite fibers. The effects of two EtOH coagulation baths maintained at −5 and 25 °C, respectively, on the morphology, structure, and mechanical properties of the composite fibers were investigated. The results show that gel spinning at −5 °C led to a relatively large shrinkage ratio, thin diameter, and low porosity of the as‐spun fibers. Simultaneously, the low coagulation temperature also greatly contributed to the formation and preservation of the liquid‐crystalline phase of the GO sheets and interrupted the crystalline zone of PVA less. As a result, either the tenacity or the elongation at break of the fibers spun at −5 °C was higher than those of the fibers spun through a coagulation bath at 25 °C. In particular, 1 wt % GO showed the highest reinforcement effects among all of the wet‐spun composite fibers. Hence, controlling the gelling–demixing process at a low temperature will provide more instructive insights for tailoring functional industrial textiles with excellent mechanical properties. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45463. Abstract :